2023
DOI: 10.5455/njppp.2023.13.06303202312062023
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on junk food consumption and nutritional status among adolescents attending Medical College and Hospital, Kolkata

Abstract: Background: This study was conducted to evaluate the pattern of junk food consumption. Junk food is defined as readily available, frequently affordable, and lacking in nutritional value. Aims and Objectives: This study is aimed to investigate the pattern of junk food eating and its consequences on the nutritional status of the adolescents. Materials and Methods: This is an institution-based cross-sectional study which was conducted at adolescent clinic from September to November 2022. Data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast, the inclination for Pepsi or Coke was comparatively lower among college students when compared to alternative fast food selections. Manna et al (2023) An epidemiological study on junk food consumption and nutritional status among adolescents attending Medical College and Hospital, Kolkata This study revealed that 82.02% of the respondents had taken junk food within the past week. Around 49.32% of the respondents opted for junk food consumption within their family circle (47.95%) and at their homes (47.95%).…”
Section: Yarmohammadi Et Al (2015)mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the inclination for Pepsi or Coke was comparatively lower among college students when compared to alternative fast food selections. Manna et al (2023) An epidemiological study on junk food consumption and nutritional status among adolescents attending Medical College and Hospital, Kolkata This study revealed that 82.02% of the respondents had taken junk food within the past week. Around 49.32% of the respondents opted for junk food consumption within their family circle (47.95%) and at their homes (47.95%).…”
Section: Yarmohammadi Et Al (2015)mentioning
confidence: 97%
“…Moreover, 46% of the respondents do incorporate fast food into their diet but can't be categorized as regular consumers (Jayasinghe & De Silva, 2014). Another study also demonstrates that the majority of the respondents (82.02%) had ingested junk food within the past 7 days, with 10.96% of them having consumed junk food more than three times in the previous week (Manna et al, 2023).Likewise, Althubaiti (2022) found that 42.1% of the female respondents consumed junk food at weekend. Furthermore, Merely 3% of females and 5% of males reported daily consumption of fast foods, while 38% of females and 51% of males indulged in fast food on a weekly basis (Anitha et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%